Crystal structure of a one-dimensional coordination polymer of gadolinium dibromoacetate with 4,4'-bipyridine - Sieron, Leslaw; Czylkowska, Agnieszka; Rogalewicz, Bartlomiej (European Journal of Chemistry, 2018)
A new gadolinium(III) complex with 4,4’-bipyridine (4-bpy) and dibromoacetate ligand of general formula [Gd(4-bpy)(CBr2HCOO)3(H2O)]n, has been synthesized, crystallized and characterized by a single-crystal X-ray diffraction analysis. The gadolinium atom has an unsymmetrical eight-coordinate geometry, being coordinated by six oxygen atoms of dibromoacetate anions, one nitrogen atom of 4-bpy and one water molecule. The complex is a one-dimensional polymer as a result of dibromoacetate ligand bridging with the repeating monomeric units. There are π...π stacking interactions between the 4-bpy rings as well as O–H...O and O–H...N hydrogen bonds. Crystal Data for C16H13Br6GdN2O7 (Mw = 981.99 g/mol): triclinic, space group P-1 (no. 2), a = 9.7368(4) Å, b = 11.5416(4) Å, c = 11.7634(4) Å, α = 104.2750(10)°, β = 94.060(2)°, γ = 92.6900(10)°, V = 1275.08(8) Å3, Z = 2, T = 90 K, μ(CuKα) = 28.190 mm-1, Dcalc = 2.558 g/cm3, 8399 reflections measured (7.782° ≤ 2Θ ≤ 133.18°), 4006 unique (Rint = 0.0409, Rsigma = 0.0639) which were used in all calculations. The final R1 was 0.0527 (I > 2σ(I)) and wR2 was 0.1396 (all data).